Perbandingan Hasil Koordinat Kerangka Pemetaan Menggunakan Metode Bowditch Poligon Tertutup Dengan Metode Adjustment Triangulated Quadrilateral - Farouki Dinda Rassarandi; Oktavianto Gustin; Putra Putra (Politeknik Negeri Batam, 2021)
The basic mapping framework is divided into two types: the horizontal framework (planimetric) and the vertical framework (height). The basic horizontal framework of mapping varies depending on the selection and usability policy determined by many factors, which as the area, tools availability, and the calculation method. The geodesy field's commonly used basic mapping frameworks are triangulation and polygon methods. A least-squares calculation method or a least-squares triangulation adjustment can be used to obtain the precise map frame coordinate value from the triangulation method measurement results. On the other hand, the polygon method uses Bowditch to solve the problem. The least-squares method (adjustment) is well known as the three methods. There are parameters, conditions, and combinations. The least-squares method of triangulation (triangulated quadrilateral adjustment) can use the conditions or measurements equation either azimuth or angle measurement. The procedure of this equation involves parameter adjustment, where these parameters are the coordinates on a flat surface. This study compares the coordinate result of the enclosed polygon mapping framework between the Bowditch method and the Adjustment Triangulated Quadrilateral method. The coordinates result of the calculations using the Bowditch method provides value better than the adjustment method, where the confidence interval of the standard deviation of the coordinates using this method is around 0.400954085 ft minimum and 1.020967284 ft maximum in the 90% of a confidential level, in the other hand, the adjustment method ranges between 1.112780078 ft minimum and 2.833521575 ft maximum.